2003
DOI: 10.2307/3558982
|View full text |Cite
|
Sign up to set email alerts
|

Food Stamps and the Elderly: Why Is Participation so Low?

Abstract: Estimates imply that only one-third of elderly persons who are eligible for food stamps actually participate in the program, which is half the rate that exists among younger people. This study investigates potential reasons for the relatively low take-up rate among the elderly. Analyzing new data, we conclude that the low take-up rate is not explained by measurement error and little is explained by various behavioral factors.Despite this much lower take-up rate, elderly who are eligible for assistance but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 12 publications
10
98
0
Order By: Relevance
“…Several other studies have reported lower participation rates among the elderly (6,9) . In the CWHS, older women cite reasons related to lack of information for not applying more often than stigma.…”
Section: Discussionmentioning
confidence: 90%
“…Several other studies have reported lower participation rates among the elderly (6,9) . In the CWHS, older women cite reasons related to lack of information for not applying more often than stigma.…”
Section: Discussionmentioning
confidence: 90%
“…The estimators for binary choice models with misreporting (Bollinger and David, 1997; require predicted probabilities of misreporting for each individual. Analyses of program take-up such as Haider, Jacknowitz and Schoeni (2003) could avoid the bias in their estimates by calculating these probabilities fromf…”
Section: Conditional Density Methodsmentioning
confidence: 99%
“…However, as I show in section 5, obtaining consistent estimates from public use data is simple if information about the relation between true and observed variables is available. Studies of program take-up (e.g., Currie and Grogger, 2001;Haider, Jacknowitz and Schoeni, 2003;Currie, 2004) use reported receipt as the dependent variable in binary choice models. Bollinger and David (1997) and Meyer, Goerge and Mittag (2012) find significant bias due to misreporting in probit models.…”
Section: Misreporting Of Government Programs and Its Consequencesmentioning
confidence: 99%
“…1 Some examples include McGarry 1996;Choi 1998;Davies 2002;Haider, Jacknowitz, and Schoeni 2003;Levy 2008;and Wu 2009. 2 There are some very recent variations in eligibility rules across states for the SNAP.…”
Section: Using the Health And Retirement Study (Hrs) Linked To Adminimentioning
confidence: 99%
“…Low take-up by the elderly in most means-tested transfer programs is a persistent and puzzling phenomenon: estimated elderly take-up rates for Supplement Security Income (SSI) range from 38 to 73 percent (for example, Coe 1983;Shields et al 1990;McGarry 1996;Strand, Rupp, and Davies 2009) and less than 35 percent for the Supplementary Nutrition Assistance Program (SNAP) (Haider, Jacknowitz, and Schoeni 2003;Wolkwitz and Leftin 2008;Wu 2009). …”
Section: Introductionmentioning
confidence: 99%